Implementation of Love Based Curriculum in Character Development of Students In Modern Islamic Boarding Schools - Harahap, Muhammad Yunan; Lubis, Sakban; Harahap, Abdi Syahrial (STAI Serdang Lubuk Pakam, 2025)
This study aims to explore the implementation of a love-based curriculum in developing the character of santri at Pondok Pesantren Modern Darul Ulum Al-Muhajirin, Langkat Regency. This curriculum integrates five main values, namely love for Allah, the Messenger of Allah, knowledge, fellow humans, and the homeland, which are applied in various aspects of pesantren life. The method used in this research is a qualitative approach with a case study design, which involves in-depth interviews, participatory observation, and documentation. The results showed that the love-based curriculum succeeded in shaping the character of better santri, with improvements in discipline, empathy, social responsibility, and love for knowledge and the homeland. Although the implementation of this curriculum shows positive results, the main challenge faced is the influence of globalization and technology that often conflicts with pesantren values. Overall, the love-based curriculum at Pondok Pesantren Modern Darul Ulum Al-Muhajirin can be an effective model in developing the character of students, who are not only academically intelligent, but also have noble character and care for others and the homeland.